Quantitative Phase Analysis of the Calcium Silicate Slag as the Residue of Extracting Alumina from High-Alumina Fly Ash - 黄冬波 宗燕兵 刘晓明 彭丹丹 杨志杰 (Shanghai jiao tong da xue xue bao, 2016)
Calcium silicate slag is the residue of process of pre-desilication alkali lime sintering applied in the high-alumina fly ash to extract the alumina. The quantitative phase analysis （QPA） of the calcium silicate slag has been performed by the Rietveld method based on the powder X-ray diffraction （XRD） with the aid of non- commercial software GSAS-EXPGUI. A known weight of crystalline internal standard （10% CaF2） was added to the calcium silicate slag to calculate the fraction of amorphous phase and other crystalline phases on an absolute basis. Besides, the calcium silicate slag was characterized by X-ray fluorescence （XRF） and thermo gravimetric （TG） differential scanning calorimetry （DSC） to test the QPA results and investigate its other characters. Finally, the results show that the amorphous fraction is 17.5% （hereinafter, the percentages refer to the mass fraction）, and the major crystalline phases detected in the calcium silicate slag consist of 23.5% Beta-Ca2SiO4, 10,0% bredigite, 10.3% Ca3A12Oa （C3A） and 21.6% CaCO3.